2016
DOI: 10.4103/2231-0762.197198
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the clinical assessment of impacted mandibular third molars with panoramic radiograph and intraoral periapical radiograph

Abstract: Aims And Objectives:This study was conducted to compare the clinical assessment of impacted third molars of mandible with panaromic radiograph (OPG) and intraoral periapical radiograph (IOPA) and to assess the efficacy of IOPA and. Moreover, we corroborated the OPG and IOPA findings of impacted mandiblar third molar root apex to inferior alveolar canal.Materials and Methods:A total of 200 patients with pericoronitis were examined who were indicated for surgical extraction, among which 50 patients were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In order to evaluate patterns of third molars Orthopantomogram (OPG) is most commonly used radiographic investigation. 4 We can assess the type of impaction, depth, it's relation to adjacent tooth, maxillary sinus and the Inferior alveolar canal (IAC), to plan the management accordingly. Many studies have shown that the presence of impacted 3 rd mandibular molar may lead to various complications including infections, odontogenic cysts/tumors and even fracture at the mandibular angle region 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate patterns of third molars Orthopantomogram (OPG) is most commonly used radiographic investigation. 4 We can assess the type of impaction, depth, it's relation to adjacent tooth, maxillary sinus and the Inferior alveolar canal (IAC), to plan the management accordingly. Many studies have shown that the presence of impacted 3 rd mandibular molar may lead to various complications including infections, odontogenic cysts/tumors and even fracture at the mandibular angle region 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Analyses on orientations of impacted mandibular third molars expressed that mesioangular kind of impaction was the most incessantly viewed. 4,14,15 This inquiry revealed that mesioangular inclination is the most noticeable angulation though not with an explicit tiein to the age classes (p >0.05). This outcome acceded to that from foregoing inquiries.…”
Section: Discussionmentioning
confidence: 82%
“…This affirmed the deductions of other inquirers. 1,2,4 Acute pericoronitis is a recurring indication for taking out impacted inferior third molars in this disquisition. This was in accordance with reports from other acquisitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations